2009
DOI: 10.1242/jeb.022640
|View full text |Cite
|
Sign up to set email alerts
|

Peak energy turnover in lactating European hares: the role of fat reserves

Abstract: SUMMARYEuropean hares (Lepus europaeus) in central Europe have high energetic costs of reproduction, mainly due to precocial, rapidly growing young that rely largely on energy-rich milk. Thus, hares in this climate build up large fat stores during winter that are then gradually depleted during the spring-to-autumn breeding season. We hypothesized that the diminishing fat stores of females over the breeding season might affect resource allocation, peak energy assimilation during lactation or the total investmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
58
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 32 publications
9
58
2
Order By: Relevance
“…Lactation is the most energy-demanding state in the lifetime of most female mammals, which in small mammals is met primarily by increasing energy intake (Hammond and Kristan, 2000;Król and Speakman, 2003;Rogowitz, 1998;Speakman and Król, 2005;Valencak et al, 2009Valencak et al, , 2010Weiner, 1992). In the present study, energy intake increased by 292.8% in lactating hamsters compared with the non-reproductive group.…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…Lactation is the most energy-demanding state in the lifetime of most female mammals, which in small mammals is met primarily by increasing energy intake (Hammond and Kristan, 2000;Król and Speakman, 2003;Rogowitz, 1998;Speakman and Król, 2005;Valencak et al, 2009Valencak et al, , 2010Weiner, 1992). In the present study, energy intake increased by 292.8% in lactating hamsters compared with the non-reproductive group.…”
Section: Discussionsupporting
confidence: 42%
“…Although digestive plasticity is used by females to meet the energetic demands of lactation, a limit to sustained energy intake (SusEI) or total energy expenditure exists during peak lactation (Hammond and Diamond, 1992;Hammond et al, , 1996Król and Speakman, 2003;Król et al, 2003;Rogowitz, 1998;Valencak et al, 2009Valencak et al, , 2010Weiner, 1992). During the search for the mechanism behind limitations on SusEI, studies focused on several hypotheses, one of which is the central limitation hypothesis (Koteja, 1996b;Simons et al, 2011;Król, 2005, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Although fat stores may have contributed relatively little to overall lactation performance in the current study, we do not mean to imply this low contribution is the same in all small mammals. Valencak and colleagues, for example, found that female brown hares (Lepus europaeus) adjusted their investment in their young in relation to the size of their fat reserves (Valencak et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…We have also seen that free-living birds, except in the case of the marathon migrants, generally do not work harder than this either. The considerable gap between the maximum sustained working level of 4 or 5 times BMR that hard-working parent birds are prepared to give (Drent and Daan, 1980) and the physiological maxima of 7-10 times BMR that can be achieved under exceptional conditions makes evolutionary sense if working hard comes at a survival cost (Valencak et al, 2009). My reading of the literature suggests that any kind of hard work, perhaps above taxon-(or rather, ecology-) dependent thresholds (Speakman et al, 2002;Speakman, 2005;Furness and Speakman, 2008), comes with wear and tear.…”
Section: Protecting Long-term Fitness Assets: the Evolution Of Lazinessmentioning
confidence: 99%
“…My reading of the literature suggests that any kind of hard work, perhaps above taxon-(or rather, ecology-) dependent thresholds (Speakman et al, 2002;Speakman, 2005;Furness and Speakman, 2008), comes with wear and tear. A precipitous increase in the likelihood of organ or performance failure, and mortality associated with increases in energy expenditure (Ricklefs, 2008), would explain why animals are reluctant to habitually spend as much as they are physiologically capable of (Valencak et al, 2009); that is, if such precipitous increases the likelihood of death are not compensated for by increases in reproductive output (Williams, 1966;Lessells, 1991;Daan and Tinbergen, 1997). Evolutionary trade-offs would then select for animals that are not prepared to work harder than what we heuristically called the optimal working capacity (Fig.4) (Royama, 1966).…”
Section: Protecting Long-term Fitness Assets: the Evolution Of Lazinessmentioning
confidence: 99%